2023
DOI: 10.1186/s13048-023-01187-1
|View full text |Cite
|
Sign up to set email alerts
|

BCAS2 regulates granulosa cell survival by participating in mRNA alternative splicing

Abstract: Background Granulosa cell proliferation and differentiation are essential for follicle development. Breast cancer amplified sequence 2 (BCAS2) is necessary for spermatogenesis, oocyte development, and maintaining the genome integrity of early embryos in mice. However, the function of BCAS2 in granulosa cells is still unknown. Results We show that conditional disruption of Bcas2 in granulosa cells caused follicle development failure; the ratio of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Moreover, at 5dpp, the positive TUNEL signal in cKO ovaries was significantly increased compared with that in the control, which indicated that apoptosis occurred in the primordial follicles (Figure 5G,H). In addition, our previous studies demonstrated that Bcas2 is involved in splicing precursor mRNAs through the CDC5L/PRP19 complex 25 . The fluorescence intensity of CDC5L and PRP19 with VASA was diminished in oocytes, suggesting that BCAS2 may regulate the AS of Dazl and Diaph2 through the CDC5L/PRP19 complex (Figure 5I), which in turn affects oogenesis.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, at 5dpp, the positive TUNEL signal in cKO ovaries was significantly increased compared with that in the control, which indicated that apoptosis occurred in the primordial follicles (Figure 5G,H). In addition, our previous studies demonstrated that Bcas2 is involved in splicing precursor mRNAs through the CDC5L/PRP19 complex 25 . The fluorescence intensity of CDC5L and PRP19 with VASA was diminished in oocytes, suggesting that BCAS2 may regulate the AS of Dazl and Diaph2 through the CDC5L/PRP19 complex (Figure 5I), which in turn affects oogenesis.…”
Section: Resultsmentioning
confidence: 79%
“…Primordial follicles and primary follicles were counted and classified in every fifth section, the total number of follicles was multiplied by five. Secondary follicles and antral follicles were counted by scanning all sections, and the follicles were counted in all sections with clear oocyte nuclei 25–28 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation